Optimizing the Utilization of Reading Corners as an Effort to Improve Students' Reading Literacy at MI Negeri 2 Banjarmasin - Aprianti, Henny; Hasriani (Jurnal Profesi Guru Indonesia, 2025)
This study aims to analyze the impact of using a reading corner as an effort to improve students' reading literacy at MIN 2 Banjarmasin. This study uses a mixed research approach with the type of classroom action research. The design used is the Kurt Lewin model with four stages, namely planning, action, observation and reflection. The subjects of this study were students of MIN 2 Banjarmasin. The data for this study were obtained using questionnaire and observation techniques. The questionnaire was used to analyze the advantages and disadvantages of the reading corner that was created so that it could be improved and observation was used to analyze the impact of the reading corner on improving students' reading literacy. The data analysis technique used in this study was descriptive statistics by comparing the results obtained with indicators of research success. The results showed that the use of a reading corner can improve students' reading literacy at MIN 2 Banjarmasin. This can be seen from the increase in the percentage of students' reading literacy in each cycle with details of the pre-cycle 48.71%, the first cycle 66.39% and in the second cycle it increased to 89.66%. Thus, the use of a reading corner can be used as an alternative to improve students' reading literacy.